From listeners to changemakers: Transforming sheep fattening through native-language radio programs and knowledge networks - Ekule, Muluken; Wamatu, Jane; Abiso, Tesfaye (International Center for Agricultural Research in the Dry Areas, 2024)
Broadcasting innovations in livestock production through native-language radio programs are crucial for effective communication with farmers. It is an effective tool to promote agriculture and development in rural areas and facilitate knowledge sharing and peer learning among farmers. Broadcasting in the native language ensures easy understanding, overcomes language barriers, and enhances the relevance and impact of communication